EEJ and EIA variations during modeling substorms with different onset moments. Issue 9 (1st November 2015) - Klimenko, V.V.; Klimenko, M.V.
Abstract This paper presents the simulations of four modeling substorms with different moment of substorm onset at 00:00 UT, 06:00 UT, 12:00 UT, and 18:00 UT for spring equinoctial conditions in solar activity minimum. Such investigation provides opportunity to examine the longitudinal dependence of ionospheric response to geomagnetic substorms. Model runs were performed using modified Global Self-consistent Model of the Thermosphere, Ionosphere and Protonosphere (GSM TIP). We analyzed GSM TIP simulated global distributions of foF2, low latitude electric field and ionospheric currents at geomagnetic equator and their disturbances at different UT moments substorms. We considered in more detail the variations in equatorial ionization anomaly, equatorial electrojet and counter equatorial electrojet during substorms. It is shown that: (1) the effects in EIA, EEJ and CEJ strongly depend on the substorm onset moment; (2) disturbances in equatorial zonal current density during substorm has significant longitudinal dependence; (3) the observed controversy on the equatorial ionospheric electric field signature of substorms can depend on the substorm onset moments, i.e., on the longitudinal variability in parameters of the thermosphere–ionosphere system.